The indirect influence of quasars on reionization. (3rd July 2018) - Seiler, Jacob; Hutter, Anne; Sinha, Manodeep; Croton, Darren
ABSTRACT: The exact role of quasars during the Epoch of Reionization remains uncertain. With consensus leaning towards quasars producing a negligible amount of ionizing photons, we pose an alternate question: Can quasars indirectly contribute to reionization by allowing ionizing photons from stars to escape more easily? Using the semi-analytic galaxy evolution model to evolve a galaxy population through cosmic time, we construct an idealized scenario in which the escape fraction of stellar ionizing photons ( f esc ) is boosted following quasar wind events, potentially for several dynamical times. We find that under this scenario, the mean value of f esc as a function of galaxy stellar mass peaks for intermediate mass galaxies. This mass dependence will have consequences for the 21-cm power spectrum, enhancing power at small scales and suppressing it at large scales. This hints that whilst quasars may not directly contribute to the ionizing photon budget, they could influence reionization indirectly by altering the topology of ionized regions.